A case of Sheehan syndrome in early pregnancy - Nikumbhe, Rahul Daulat; Kamble, Bhimrao Gyanba; Khan, Sufiyan Afsar; Agarkar, Aniket Dineshrao (International Journal of Research in Medical Sciences, 2025)
Sheehan syndrome is also known as hypopituitarism due to necrosis of the anterior pituitary gland due to hypotension or shock, secondary to postpartum bleeding. It generally occurs in postpartum bleeding after a full-term delivery as there is physiological hyperplasia of the pituitary gland which demands more blood supply. After severe postpartum haemorrhage, there is inadequate blood supply to the pituitary gland which results in necrosis of the gland. The first and most common symptom of Sheehan syndrome is absence of lactation. Other symptoms may include amenorrhoea, hot flashes. Sheehan syndrome is still a significant cause of morbidity and mortality in less developed countries. The diagnosis of Sheehan syndrome may not present immediately after birth. But rarely, it can be seen in the first trimester due to incomplete abortion. In our case a 35-year female G5P4L4 with one month and fifteen days of amenorrhoea came with complain of bleeding per vaginal and severe generalised weakness. After stabilisation patient was evaluated and it came to know that patient has hypopituitarism.